Lectotypifications and taxonomic notes in the Stenorrhynchos clade (Spiranthinae, Orchidaceae) - Guimarães, Leonardo R. S.; Salazar, Gerardo A.; de Barros, Fábio (Phytotaxa, 2019)
We propose fourteen lectotypifications and five new synonyms for species in the Stenorrhynchos clade, one of the four major lineages of subtribe Spiranthinae. Also, one species of Eltroplectris, one of Sacoila and one of Stenorrhynchos are indicated as incertae sedis.